2020
DOI: 10.3390/jtaer16030023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cloud-Based Bookstore Continuance from a Deconstructed Task–Technology Fit Perspective

Abstract: In an effort to help organizations understand consumers, our study deconstructs task–technology fit into two segments: ideal task–technology fit and individual use context–technology fit. Users’ continuous use of cloud-based bookstores is studied through survey methodology to collect consumer experience data related to the use of such cloud-based bookstores. In total, 185 samples were collected. Analytical results demonstrated that both ideal task–technology fit and individual use context–technology fit were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Lavaan aims to appeal to a large group of applied researchers who need SEM to implement a new methodological idea and is an open-source program (Rosseel, 2012). The Lavaan is a SEM technique that provides the use of the R language (Hung et al , 2020). Also, lavaan is preferred for complex models with all the features of R (Thakkar, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Lavaan aims to appeal to a large group of applied researchers who need SEM to implement a new methodological idea and is an open-source program (Rosseel, 2012). The Lavaan is a SEM technique that provides the use of the R language (Hung et al , 2020). Also, lavaan is preferred for complex models with all the features of R (Thakkar, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The Original and Updated TTF Models Goodhue (1998) developed the TTF model to explain the relationship between technology and consumers' acceptance, performance (Hung et al, 2021), and use (Kim et al, 2010). The TTF model refers to the characteristics of technologies and tasks, and how they fit together.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TTF model refers to the characteristics of technologies and tasks, and how they fit together. In addition, the TTF model can also be explained as matching technological capabilities to task demands ( Kim et al, 2015 ) or as the extent to which technological tools can help individuals to complete their tasks ( Hung et al, 2021 ). The TTF model is used widely in analyzing use intentions for digital libraries, health care, and decision-making, in addition to the effects on performance, attitudes, and beliefs ( McGill and Klobas, 2009 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Precisely, current research trends on CC have sought to study the technology's acceptance or adoption; however, little research attention has been given to the continuance use, particularly at organizational-level setting [14][15][16][17]. In the context of HEIs, past research has also reported that evidence on continuance of CC at individual and organizational level is scarce [10,[18][19][20][21][22]. Therefore, answering to the following research questions was an apparent motivation for this research to be conducted: (i) What constructs influence the organizational-level continuance of CC in HEIs?…”
Section: Introductionmentioning
confidence: 99%